Carbon Emissions as a Moderator of Board Characteristics and Cost of Debt - Sillvyana Budiarto; Tan Ming Kuang (Owner : Riset dan Jurnal Akuntansi, 2025)
This study investigates how carbon emissions moderate the relationship between board characteristics and cost of debt in Indonesia's two-tier corporate governance system. A total of 612 firm-year observations were collected from 204 non-financial companies that were incorporated in the Indonesia Stock Exchange (IDX) from the year 2020 to 2022. Using Moderated Regression Analysis (MRA), the study demonstrates that the cost of debt is unrelated to the number of women on the board and the independence of commissioners. However, this finding indicates that carbon emissions moderate the influence of gender diversity on cost of debt. Employing Robustness Standard Errors, the study's findings are solid. The outcome of this research implies that board members and management may use this information to manage loan expenses by hiring more women. It is suggested that women on the board are more aware of environmental performance, which could lower the cost of debt for companies with low carbon emissions.